Technology, Trade and Inequality - Roger Bjørnstad; Terje Skjerpen (Statistics Norway, Research Department, 2003)
In recent decades new technology has led to increasing demand for well-educated labour at the expense of labour with lower education levels. Moreover, increased imports from low-cost countries have squeezed out many Norwegian manufacturing firms employing a sizeable share of workers with low education. In this article a large macroeconomic model for Norway (MODAG) is used to quantify the importance that technological developments and competition from low-cost countries have had for the economy and for low- and high-educated labour. The results show that above all technological developments, but also increased trade with low-cost countries, have reduced demand for low-educated labour relative to well-educated labour. Wage formation factors have however meant a) that technological developments have also benefited those with low education who still hold a job, and b) that a relative fall in prices on goods from poor parts of the world has kept down wage differentials.
Keywords: E24; E27; F16; O33; 330; Skill-bias technological change; international trade; centralized wage setting; inequality; labour demand; macroeconometric model.